The influence of endocrine disrupting chemicals - Pawłowski, Bartosz; Sienkiewicz, Michał; Kłusek , Magdalena; Zatłoka-Mazur, Dorota; Żybowska-Męczyńska, Monika; Klimas, Filip; Sienkiewicz, Bartłomiej; Rusiński, Kacper; Potoczek , Adriana (Quality in Sport, 2025)
On a daily basis, everyone is exposed to many chemical compounds that have been classified as endocrine disrupting chemicals (EDCs). These are natural and artificially produced substances that are widely available in the environment today. The aim of the study is to determine the effect of endocrine disrupting chemicals on hormonal processes occurring in the human body and to determine their mechanisms of action. The research method used was a literature review on the Pubmed platform. Studies show that EDCs affect prenatal growth, thyroid function, glucose metabolism, obesity development, and puberty and fertility processes by mimicking hormones naturally occurring in the human body, which very often leads to disorders in the hormonal axis at various levels. Recent research reports say that EDCs interact through epigenetic mechanisms. These substances are considered safe individually, but the subject of research remains the "cocktail effect", which consists in exposing several EDCs to the body at the same time. The key here is to limit human contact with these substances as much as possible. Studies have so far proven the negativin effects of many of them on our body, but many of the long-term effects have yet to be studied. Fortunately, more and more countries are introducing restrictions on the use of these substances and are looking for methods to replace them with less harmful substitutes. Further research is needed to understand the effects of these substances on humans, which will further enable the development of appropriate regulation of EDCs.